2015
DOI: 10.1038/nmat4340
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation locking versus easy glide in titanium and zirconium

Abstract: The ease of a metal to deform plastically in selected crystallographic planes depends on the core structure of its dislocations. As the latter is controlled by electronic interactions, metals with the same valence electron configuration usually exhibit a similar plastic behaviour. For this reason, titanium and zirconium, two transition metals of technological importance from the same column of the periodic table, have so far been assumed to deform in a similar fashion. However, we show here, using in situ tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 30 publications
20
79
0
Order By: Relevance
“…The work here provides quantitative results for Mg, which can be made even more quantitative with additional firstprinciples studies, and provides a firm basis for future quantitative work on Ti, Zr, and other hcp metals. Combined with other recent works (54,61,62), computational metallurgy is now revealing the rich, distinct, and complex behavior in a class of materials, hcp metals, that have high technological value.…”
Section: Discussionmentioning
confidence: 91%
“…The work here provides quantitative results for Mg, which can be made even more quantitative with additional firstprinciples studies, and provides a firm basis for future quantitative work on Ti, Zr, and other hcp metals. Combined with other recent works (54,61,62), computational metallurgy is now revealing the rich, distinct, and complex behavior in a class of materials, hcp metals, that have high technological value.…”
Section: Discussionmentioning
confidence: 91%
“…While SF energy calculations with full relaxations are emerging, there has been no complete examination of the true stable SF energies, positions, and structures on all relevant slip planes across the family of hcp metals. Accurate SF energies and structures on Prism and Pyramidal planes are particularly important for understanding/prediction of the core structure, dissociation, and stability of c and c + a dislocations, for which direct DFT simulations remain challenging although not impossible [16,9,18,19]. In this work, we perform DFT calculations with full atomic (ionic) relaxation to find all the stable SFs on all the slip planes relevant to plastic deformation of hcp metals.…”
mentioning
confidence: 99%
“…However, it was shown by an in situ transmission electron microscopy strain study and firstprinciples calculations that Ti and Zr, have the same valence, yet have different plasticity behavior due to the inversion of stability between the glissile and sessile dislocation cores. 31 Yu et al have reported their study from first-principles theory that the profound hardening of hcp Ti by O impurities is due to the strong chemical interaction of O with the core of the dislocation. 16 These results underline the important role of chemical hybridization in components of the alloy.…”
Section: Introductionmentioning
confidence: 99%